Tailored Nanoparticles With the Potential to Reduce Ruminant Methane Emissions - Altermann, Eric; Reilly, Kerri; Young, Wayne; Ronimus, Ron S.; Muetzel, Stefan (Frontiers in Microbiology, 2022)
Agricultural methane produced by archaea in the forestomach of ruminants is a key contributor to rising levels of greenhouse gases leading to climate change. Functionalized biological polyhydroxybutyrate (PHB) nanoparticles offer a new concept for the reduction of enteric methane emissions by inhibiting rumen methanogens. Nanoparticles were functionalized in vivo with an archaeal virus lytic enzyme, PeiR, active against a range of rumen Methanobrevibacter species. The impact of functionalized nanoparticles against rumen methanogens was demonstrated in pure cultures, in rumen batch and continuous flow rumen models yielding methane reduction of up to 15% over 11 days in the most complex system. We further present evidence of biological nanoparticle fermentation in a rumen environment. Elevated levels of short-chain fatty acids essential to ruminant nutrition were recorded, giving rise to a promising new strategy combining methane mitigation with a possible increase in animal productivity.